Modelling of depth stabilization and submerging of tethered underwater garage in conditions of sea oscillating motion; IOP Conference Series: Materials Science and Engineering; Vol. 327 : Mechanical Engineering, Automation and Control Systems (MEACS 2017) - Gayvoronsky S. A. Sergey Anatolievich (Simulation and automation of production engeenering, 2018)
Title screen